Potential of Islamic Insurance Market: Islamic Banking and Sukuk Sectors Case Study in Indonesia - Jaenal Effendi (Global Review of Islamic Economics and Business, 2021)
This paper predicts the potential of the Indonesian Islamic insurance market, approached by calculating the premium contribution from the Islamic banking and sukuk sectors. This paper aims to determine and analyze the potential development of Islamic insurance market in Indonesia, seen from total contributions from Islamic banking and sukuk sectors over the next five years. The paper uses the Box-Jenkins ARIMA method which is one of the quantitative forecasting methods. The results of this study indicate that over the next five years, the total contribution of Islamic insurance will experience positive growth and it is predicted that it will have a total contribution of IDR 11,568.40 billion in 2023 from Islamic banking and sukuk sectors with the biggest contributor from the Islamic banking sector. The ARIMA forecasting results show a positive trend in the premium contribution of the Islamic banking and sukuk sectors from year to year. Even so, the growth will experience a slowdown. The prediction of a slowdown in the two sectors in its contribution to the Islamic insurance market in Indonesia is a sign that there might be a decline in the total financing growth by Islamic banking. Likewise with the sukuk sector, both state and corporate sukuk are predicted to experience a slowdown in the growth of Islamic insurance premiums.